A Mediation Analysis to Identify Links between Gut Bacteria and Memory in Context of Human Milk Oligosaccharides - Stephen A. Fleming; Jonas Hauser; Jian Yan; Sharon M. Donovan; Mei Wang; Ryan N. Dilger (Microorganisms, 2021)
Elucidating relationships between the gut and brain is of intense research focus. Multiple studies have demonstrated that modulation of the intestinal environment via prebiotics or probiotics can induce cognitively beneficial effects, such as improved memory or reduced anxiety. However, the mechanisms by which either act remain largely unknown. We previously demonstrated that different types of oligosaccharides affected short- and long-term memory in distinct ways. Given that the oligosaccharide content of human milk is highly variable, and that formula-fed infants typically do not consume similar amounts or types of oligosaccharides, their potential effects on brain development warrant investigation. Herein, a mediation analysis was performed on existing datasets, including relative abundance of bacterial genera, gene expression, brain volume, and cognition in young pigs. Analyses revealed that numerous bacterial genera in both the colon and feces were related to short- and/or long-term memory. Relationships between genera and memory appeared to differ between diets. Mediating variables frequently included GABAergic and glutamatergic hippocampal gene expression. Other mediating variables included genes related to myelination, transcription factors, brain volume, and exploratory behavior. Overall, this analysis identified multiple pathways between the gut and brain, with a focus on genes related to excitatory/inhibitory neurotransmission.